2019
DOI: 10.5194/gmd-2019-200
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

P-model v1.0: An optimality-based light use efficiency model for simulating ecosystem gross primary production

Abstract: Abstract. Terrestrial photosynthesis is the basis for vegetation growth and drives the land carbon cycle. Accurately simulating gross primary production (GPP, ecosystem-level apparent photosynthesis) is key for satellite monitoring and Earth System Model predictions under climate change. While robust models exist for describing leaf-level photosynthesis, predictions diverge due to uncertain photosynthetic traits and parameters which vary on multiple spatial and temporal scales. Here, we describe and evaluate a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…An improved formulation of the cost factor 'a' can derive from recent studies that formalized the hydraulic cost/risk of delivering water from soil to leaves as an explicit set of equations that can be integrated into existing ESMs (e.g. Wolf et al, 2016 PNAS;Sperry et al, 2017 PCE;Stocker et al, 2020). As such it can include the impact of soil silt content on soil and leaf hydraulic potentials, transpiration rates, the cost of water uptake and transport by plants and, ultimately, the leaf C i /C a ratio (e.g.…”
Section: Developing the Least-cost Theory With Soil Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An improved formulation of the cost factor 'a' can derive from recent studies that formalized the hydraulic cost/risk of delivering water from soil to leaves as an explicit set of equations that can be integrated into existing ESMs (e.g. Wolf et al, 2016 PNAS;Sperry et al, 2017 PCE;Stocker et al, 2020). As such it can include the impact of soil silt content on soil and leaf hydraulic potentials, transpiration rates, the cost of water uptake and transport by plants and, ultimately, the leaf C i /C a ratio (e.g.…”
Section: Developing the Least-cost Theory With Soil Propertiesmentioning
confidence: 99%
“…This is why it has been considered to be a value optimized by natural selection (Prentice et al, 2014). The C i /C a ratio is also a pivotal physiological variable for the coupling of transpiration and photosynthesis from vegetated surfaces in relation to climate in Earth System Models (ESMs) (Wang et al, 2014;Stocker et al, 2020). The impact of soil environment on biophysical-biochemical interactions and C i /C a variation is expected to be substantial but has yet to be quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Under natural conditions, however, Φ PSII,max,dark is only relevant when leaves begin photosynthesizing at dawn. Therefore, we replaced Φ PSII,max,dark by the maximum quantum yield of photosystem II for a typical light-adapted leaf Φ PSII,max,light , which is a function of temperature (T; °C; Bernacchi, Pimentel, & Long, 2003;Stocker, Wang, et al, 2019;Wang et al, 2020):…”
Section: The Optimality Photosynthesis Modelmentioning
confidence: 99%
“…Although efforts have been made to develop water stress functions for V cmax,25C (Keenan, Sabate, & Gracia, 2010), most are empirical and thus are not incorporated into our mechanistic model to avoid over-tuning. Recent studies have indicated that parameterizing the cost ratio β (Equation 5), which varies over time as a result of varying water potential between soil and leaves, is a potential pathway to incorporate the soil moisture effect into the optimality model (Lavergne et al, 2020;Stocker, Wang, et al, 2019).…”
Section: Limitationsmentioning
confidence: 99%
“…f is the fractionation associated with photorespiration (≈12‰) and Γ * is the CO 2 compensation point in the absence of mitochondrial respiration (Bernacchi, Singsaas, Pimentel, Portis, & Long, 2001). Γ * was computed using the rpmodel R package (Stocker et al, 2019) using the average summer maximum temperature, which is representative of the temperature of the photosynthetically active period. Since no climate data were available before 1866 in our study area, 1783-1865 Γ * values were estimated using the average summer maximum temperature of the 1866-1900 period.…”
Section: Inference Of Iwue From Tree-ring Carbon Isotope Ratiosmentioning
confidence: 99%